Biomechanical evaluation of a novel hockey-stick locking plate featuring a pes anserinus-sparing design: a finite element analysis - Wang, Xiao; Lai, Haohua; Zhang, Songyan; Tu, Zhiheng; Yin, Zhaowei; Wako, Gadisa Musa; Yan, Junwei; Liang, Bin (Frontiers in Surgery, 2026)
BackgroundSurgical fixation for Schatzker IV tibial plateau fractures presents a clinical dilemma: achieving robust stability while avoiding impingement on the pes anserinus tendons. This study evaluated the biomechanical profile of a novel hockey-stick locking plate (NHLP), which is anatomically contoured to address this challenge by being placed anteriorly.MethodsA finite element model of a standardized Schatzker IV fracture was created. Three fixation methods were simulated: the novel hockey-stick locking plate (NHLP), the traditional T-shaped locking plate (TTLP), and the double reconstruction locking plates (DRLP). The models were subjected to four loading conditions: three physiological loads, a low axial load (500 N), a moderate combined load (1,500 N axial compression plus 150 N anterior shear force), and a high axial load (2,500 N) and a fourth “worst-case” load scenario combining a 1,700 N axial force, a 200 N anterior shear force, and a 10° varus tilt. Key biomechanical metrics, including implant stress, construct stability, fragment displacement, fracture interface mechanics and fatigue safety factor, were analyzed.ResultsUnder physiological loading, the NHLP construct demonstrated the lowest peak von Mises stress on the implant. At the high axial load of 2,500 N, the peak stress on the NHLP (159.8 MPa) was 15% lower than that on the TTLP (188.1 MPa) and 35% lower than that on the DRLP (245.5 MPa). In the “worst-case” scenario, all constructs exhibited high safety factors. In terms of stability, the NHLP provided displacement comparable to that of the TTLP, and both were substantially more stable than the DRLP construct, which exhibited the largest displacement under high load. Paradoxically, the DRLP construct consistently resulted in the highest degree of implant stress and the least stability. At the fracture interface, the NHLP maintained a stable environment across all loads, with key metrics remaining within a range conducive to bone healing.ConclusionThis finite element analysis demonstrated that the NHLP provides fracture stability while reducing peak implant stress under physiological loading. These findings support the biomechanical feasibility of its pes anserinus-sparing design, providing a strong rationale for further investigation.